In vitro safety of ketotifen as a topical nasal rinse. Issue 2 (22nd February 2020) - Triantafillou, Vasiliki; Maina, Ivy W.; Patel, Neil N.; Tong, Charles C. L.; Papagiannopoulos, Peter; Kohanski, Michael A.; Kennedy, David W.; Palmer, James N.; Adappa, Nithin D.; Cohen, Noam A.; Bosso, John V.
Abstract : Background: Ketotifen is a second‐generation noncompetitive H1‐antihistamine and mast‐cell stabilizer. It is commonly used to treat or prevent allergic conjunctivitis, asthma, chronic urticaria, anaphylaxis, mast‐cell, and other allergic‐type disorders. However, it has never been studied in aspirin‐exacerbated respiratory disease (AERD), an aggressive phenotype of chronic rhinosinusitis with nasal polyps, where the mast cell plays a prominent role its pathogenesis. Methods: Human sinonasal epithelial cells were grown at an air‐liquid interface (ALI). Ketotifen powder was dissolved in saline to make 4 test solutions at 1.04, 2.08, 10.4, and 20.8 µg/mL. Control (saline) or ketotifen solution was added apically to ALI cultures from tissue of 5 unique patients, and ciliary beat frequency (CBF) changes were recorded. Lactate dehydrogenase was measured at 24 and 48 hours to estimate long‐term cellular toxicity. Results: Apical application of ketotifen at all concentrations was neither ciliotoxic nor ciliostimulatory, with no change in CBF over a period of 15 minutes after application. Cellular toxicity for all concentrations at 24 and 48 hours after application was <3% and <7%, respectively, that of lysed cultures. Conclusion: Topical application of ketotifen to an in vitro model of sinonasal epithelium is safe, as evaluated by CBF and lactate dehydrogenase. Ketotifen is neither ciliotoxic nor ciliostimulatory, and no long‐term cellular toxicity was observed. Ketotifen may have promise as a topical nasal rinse in the treatment of AERD.